Laura Mack Kephart’s Letter To Leonard W. Kephart October 7, 1946 - Vann, Kristen (2020)
This edition is created from the manuscript of Laura Mack Kephart’s letter written to Leonard Kephart on October 7, 1946. In this letter, Laura Kephart shows great concern for family and careful attention to the words and arrangement of newspaper headlines and church advertisements. The first page of the letter contains general family news and updates: her granddaughter Laura’s college enrollment and an upcoming trip for Howard Riley and her sister, Julia. On the next page, Laura offers a strong condemnation of the Unitarian Church, provoked by ads she has seen in the newspaper. Additionally, she discusses the world headline of the week: the trials at Nuremburg where high-profile Nazi criminals were sentenced after WWII. The letter concludes in lighthearted correspondence in which Laura documents her schedule the day prior and gives a few more updates on family and friends living in Ithaca, New York.